2007
DOI: 10.1080/14763140601058581
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of computational fluid dynamics analysis of the passive drag of a male swimmer

Abstract: The aim of this study was to build an accurate computer-based model to study the water flow and drag force characteristics around and acting upon the human body while in a submerged streamlined position. Comparisons of total drag force were performed between an actual swimmer, a virtual computational fluid dynamics (CFD) model of the swimmer, and an actual mannequin based on the virtual model. Drag forces were determined for velocities between 1.5 m/s and 2.25 m/s (representative of the velocities demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
99
3
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(121 citation statements)
references
References 5 publications
7
99
3
8
Order By: Relevance
“…By modifying disk orientation and flow characteristics (constant or variable acceleration), they found that hand acceleration (from 2.84 to 5.84 m/s) strongly increased propulsive drag by up to 40%. Following this study, interest turned to evaluating water resistances during glide periods [54,[66][67][68][69]. Investigators scanned the swimmer's whole body and tested resistances as a function of position (arms extended at the front or along the body) and depth.…”
Section: Fluid Perturbations From Swimmer's Movementmentioning
confidence: 99%
“…By modifying disk orientation and flow characteristics (constant or variable acceleration), they found that hand acceleration (from 2.84 to 5.84 m/s) strongly increased propulsive drag by up to 40%. Following this study, interest turned to evaluating water resistances during glide periods [54,[66][67][68][69]. Investigators scanned the swimmer's whole body and tested resistances as a function of position (arms extended at the front or along the body) and depth.…”
Section: Fluid Perturbations From Swimmer's Movementmentioning
confidence: 99%
“…Comparisons of total drag force were performed between a real swimmer, a digital model of this same swimmer and a real mannequin based on the digital model. Bixler et al (2007) found drag forces determined from the digital model using numerical simulations to be within 4% of the values assessed experimentally for the mannequin, although the mannequin drag was found to be 18% less than the real swimmer drag. In fact, this study has reinforced the idea of the validity and accuracy of numerical simulations in swimming research.…”
Section: Introductionmentioning
confidence: 99%
“…It is required to discretize the spatial domain into small cells to form a volume mesh or grid, and then apply a suitable algorithm to solve the equations of motion (Marinho et al, 2010a). Additionally, several studies reported the importance of numerical simulations on testing and experimentation, reducing the total effort required in the experimental design and data acquisition (Lyttle & Keys, 2006;Bixler et al, 2007). For instance, Lyttle and Keys (2006) referred that these numerical simulations can provide answers into many complex problems that have been unobtainable using physical testing techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors suggested that the use of full body suits could reduce the total drag (pressure, wave and friction) (Toussaint et al 2002;Pendergast et al 2006). Friction drag seems to be largely influenced by the use of swimsuits; however, it represents only 10-15% of total drag (Mollendorf et al 2004;Bixler et al 2007). Added to that, these new swimsuits are very thigh fitting, thus compacting the body, eliminating air pockets (Mountjoy et al 2009) and improving the swimming coordination (Chollet et al 2010).…”
Section: Introductionmentioning
confidence: 99%